Foreign Direct Investment, Economic Growth and Unemployment: Evidence from Sri Lanka - Velnampy, T.; Achchuthan, S.; Kajananthan, R. (My University, 2014)
Purpose: Main purpose of the study is to find out the impact of foreign direct investment on economic growth and unemployment. Methodology: Secondary data which are collected from the Central bank reports of Sri Lanka have been utilized in this study. Further, this study was conducted in Sri Lankan perspective, especially on the foreign direct investment, economic growth and unemployment. Data on the foreign direct investment, economic growth and unemployment from the year 1990 to 2011 was collected for the study purpose. Findings: Based on the overall study findings, we conclude that there is no significant impact of FDI on the economic growth, which is in lowest level. In contrast, we found that, in the Sri Lankan context, there is a long run equilibrium relationship between FDI and economic growth rate. We also found that, there is a significant impact of economic growth on the unemployment. Over 40 percent impact has been found. In contrast, in the long term view, findings in the co-integration test indicated that, there is no long term relationship between economic growth and unemployment. Further, in the FDI and unemployment context, significant impact has not been found. But, in the long term view, FDI has the significant relationship with unemployment. Recommendation: FDI has strategic role to influence the economic growth and reduce the unemployment in the Sri Lankan context. In this way, we suggested that developing countries should focus primarily on foreign direct investment (FDI) as a source of external finance to enhance the economic growth and reduce the unemployment.
Keywords: Economic Growth; Developing Countries; Foreign Direct Investment; Unemployment